İMKB imalat sanayi KOBİ'lerinin karlılık ve nakit dönüşüm süreleri üzerine ampirik bir çalışma - (:unkn) unknown (My University, 2010)
0

The aim of this study is to examine the effect of working capital management on firm profitability. In accordance with this aim is used to cash conversion cycle analysis and the cash conversion cyles of Turkish SMEs in the manufacturing sector listed on the Istanbul Stock Exchange (ISE) are analysed for the year 2008. The research findings indicate that there is weak correlation between profitability, measured through Return on Assets (ROA), Return on Equity (ROE) and net profit margin, and the cash conversion cycle. Also, whether or not there is a significant difference between profitability rates and cash conversion cycle of eight sub-sector analyzed using nonparametric tests.
Cash Conversion Cycle And Profitability Of Listed Manufacturing Industry SMEs In The Ise : An Empirical Investigatıon
Keywords: Tarih